Bits of Organization - Carl Rhodes (Copenhagen Business School Press, 2009)
This book assembles some of the bits that break off in the process of this collision. It plays with the already contested boundaries 'correct images' and 'correct narratives' of a legitimate organization studies so as to attest to a destabilization of any theory and method that would desire to capture, reproduce and indoctrinate knowledge.  The book brings together a group of the most exciting, innovative and original thinkers and writers working in the field of organization studies today. These are writers who push the boundaries of innovative and unconventional work that is on the fringe of publishability as governed by prevailing standards in the dominant bastions of organization studies